Monocyte chemotactic protein-1 plays a role in ovarian dysfunction related to high-fat diet-induced obesity. (3rd July 2020) - Asemota, Obehi; Thornton, Kimberley; Merhi, Zaher; Berger, Dara S.; Williams, Lyda; Seki, Yoshinori; Du, Xiu Quan; Jindal, Sangita; Charron, Maureen J.; Buyuk, Erkan
ABSTRACT: Obesity, known to cause a systemic elevation in monocyte chemotactic protein-1 (MCP-1), adversely affects normal ovarian function. The aim of this study was to determine whether MCP-1 plays a role in ovarian dysfunction that is related to obesity induced by high-fat (HF) diet intake. Wild type (WT) C57BL/6J mice were fed either normal chow (NC) (Group 1, control group) or HF diet (Group 2). To assess whether MCP-1 is involved in HF-diet-induced ovarian dysfunction, MCP-1 knock-out mice were fed HF diet (Group 3). Body weight, body fat composition, number of oocytes collected following ovarian superovulation with gonadotropins, ovarian macrophage markers and expression of genes important in folliculogenesis and steroidogenesis were quantified in the 3 groups of animals. Animals in Group 2 gained significant body weight and body mass, produced the fewest number of oocytes following superovulation, and had significant alterations in ovarian genes involved in folliculogenesis and steroidogenesis as well as genes involved in inflammation. Although animals in Group 3 had the highest body weight and body fat composition, they produced similar number of oocytes compared to animals in Group 1 but had different ovarian gene expression compared to Group 2. These findings suggest that MCP-1 gene knockout could reverse some of the adverse effects of obesity induced by HF diet intake. Future studies assessing ovarian histology in MCP-1 knock out mouse model will confirm our findings. MCP-1 inhibition could represent a future therapeutic target to protect ovarian health from the adverse effects of HF diet ingestion.